Aperfeiçoamento de um detector de espalhamento de luz laser em baixo ângulo (LALLS in-line) para acompanhamento em tempo real do processo de extrusão - Gasparini, Thiago Manha (2015)
The morphology of extruded multiphase polymer systems is usually assessed through off-line characterization methods such as microscopy, which require much time for sample preparation and analysis of the results. This work aimed to the improvement of an optical detector to measure in real time the morphology of blends and polymeric composites in processing by extrusion, by laser light scattering at low angle (LALLS). Such equipment includes hardware and software and is based on measuring the intensity of light from a laser and is spread across and under the melt flow. The signals are collected by an array 91 of photodetectors sent to a computer, and displayed in real time on a three- dimensional plot of scattered light intensity to form a surface defined by 321 points. When analyzing the scattering profile valuable information can be determined that help to elucidate the morphology of the second phase particles. The LALLS detector was tested on bench using standard samples, which were prepared so that one of its parameters (orientation, second phase concentration, dispersed particle size or type of dispersed particle) were known. This allowed the systematic study of these samples and the detector device validation. Finally, the device was tested in real time on the extrusion process, and under different materials and operating conditions. Thus, the LALLS detector device created by the group was improved making it possible to evaluate in a practical way and in real time polymer blends in solid films and morphology of some blends and polymeric composites during extrusion.